Exposición a gases volátiles y efectos en la salud de los trabajadores del Proyecto Amazonia Viva del B61 periodo febrero 2021 – 2022. - Acosta Peñafiel, Jairo Joel (2024)
Exposure to different neurotoxic agents in the oil industry causes the appearance of neurovegetative and behavioral symptoms in the health of workers. The objective of the research was to evaluate the exposure to volatile gases and determine their incidence on the health of workers of the Amazonia Viva Project who carry out the remediation process of contaminated soil during the period February 2021-2022. The research approach was qualitative-quantitative, the type of research was conducted through a case study, being a field, observational and bibliographic research, the level of research was descriptive, the selected population was 120 workers over 20 years old, the survey and questionnaire were used as research instrument. The results identified neurotoxic effects in the 120 workers evaluated with specialized questionnaires, such as the Q16 Neurotoxic Symptoms Questionnaire, which allowed early detection, determining that 29% of workers obtained a score of 6 or more; with respect to the Neurological and Psychological Symptoms (PNF), the existence of deterioration of the cognitive sphere was verified. It was concluded that long-term exposure to volatile gases causes neurodegenerative reactions, affecting the central and peripheral nervous system.